Rare Epstein-Barr Virus–Associated Smooth Muscle Tumor in a Patient with AIDS: A Case Report. Issue 1 (January 2020) - Reddy, Manoj P.; Mosenthal, William P.; Lee, Cody S.; Durfee, Ryan A.; Pytel, Peter; Luu, Hue H.
Abstract : Case: A 34-year-old man with poorly controlled acquired immune deficiency syndrome underwent excision of a left arm mass. The histopathologic workup identified the features of an Epstein-Barr virus–associated smooth muscle tumor (EBV-SMT). The patient was readmitted 5 months later for vomiting and found to have liver metastases that were confirmed to be EBV-SMT. Six months after discharge, there was no recurrence of the arm mass or increase in the size of the liver metastases. Conclusion: Most commonly found in immunocompromised patients, EBV-SMTs are rare tumors that can be mistaken for a leiomyosarcoma.